Restoration of damaged stone walls of Kumamoto castle due to the 2016 Kumamoto Earthquake - M. Fukuda (Lowland Technology International, 2018)
The 2017 Kumamoto earthquake caused damages to many stone walls of Kumamoto castle. Paper shows facing curves of deformed or collapsed stone walls can be interpreted comparing with the traditional guideline contributed to the stone piling technique. Reconstruction works are aimed to return the collapsed stone wall to the original features. The original curve of stone wall is possibly evaluated at the remained stone wall adding the existing measurement data. There were many deformed stone wall of Kumamoto castle before the 2016 Kumamoto earthquake. The stone wall is congenitally fragile to deform. Deformation level is evaluated comparing the deformed curve of stone wall and the traditional stone piling guidelinel. Stability analysis of stone wall should include deflected facings of stone wall. Paper shows the role of depth of stone wall on the base of thin skeleton model of stability analysis.